A review of flipped learning in innovative math education - Naufal Ishartono; Siti Hajar Halili; Rafiza Abdul Razak (Institute of Advanced Engineering and Science, 2023)
Many systematic reviews have examined flipped learning models in various fields. However, there is little research on the use of the flipped learning model in mathematics education, which could help researchers and practitioners use and develop a model to implement mathematics learning processes. To fill this gap, this study aimed to analyze and synthesize current knowledge and practices in the implementation of flipped learning in mathematics education. Systematic literature review was adopted as the research method following an article selection and screening process using the preferred reporting items for systematic review and meta-analysis (PRISMA) protocol. Articles published from 2012 to 2021 in some reputable databases (Web of Science, Scopus, and ERIC) were reviewed, and 17 of 137 articles were included for detailed analysis and synthesis. The findings of this study showed that research in the implementation of the flipped learning model in mathematics education focused on documenting the affectivity of the implementation of the flipped learning model, developing learning processes, and sharing preliminary findings and student feedback. Future research is highly recommended to examine different aspects of flipped learning implementation, promote longitudinal data based on multi-year research for implementing flipped learning, and review various learning media to strengthen students’ understanding of mathematics.